Pelatihan Kesehatan Kerja Kepada Pemangku Di Kota Denpasar - Purnamawati, Dr. Made Sri Putri; I Made Dwitayasa; Wika, I Made; Ni Ketut; Dewi, Ni Made Umi Kartika; Wiguna, I Nyoman Agus Pradnya; Suputra, I Kadek Darmo; Diaris, Ni Made; Kartika, I Gusti Agung Ayu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Occupational health is very much needed by stakeholders because of the prevalence of infectious diseases due to the spread of globalization. Stakeholders are very vulnerable to disease transmission because they are face to face and even come into contact with the community. In addition, stakeholders need an understanding of religious knowledge because in general stakeholders carry out professions because of heredity so that they need to be given guidance so that they have an understanding of the function, meaning of the profession and ritual ceremonies. Community service carried out by the health yoga study program aims to provide guidance and training to stakeholders in Denpasar City both from the social, religious and health aspects so that stakeholders can follow modernity standards, especially in the health sector without losing the sanctity and meaning of religious ceremonies or yadnya. The implementation methods for this activity are method I (presentation), method II (demonstration), method III (demonstrations and distribution of materials/tools) and method IV (demonstration). The results of the evaluation at the end of this activity, there was a significant increase in knowledge of the participants with the average posttest score above 90 points. In general, the implementation of this service was well received by the participants and went smoothly. Obstacles such as the schedule of activities that clash with holy holidays and the limited space for the implementation can be overcome through good cooperation from all parties. During the service, it was found that the enthusiasm of the participants to deepen the teachings of Hinduism and knowledge related to health was very high.